Interaction Effect Between Loan Officers’ Characteristics and Loan Default Rate on Crowdfunding Approval - Kavishe, Wilfred Felix; Ndaki, NsubiliIsaga Pascal; Ndaki, Daudi Pascal (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2024)
MicroFinance Institution (MFI) officers screen loans for a prosocial crowdfunding campaign in developing economies. However, loan officers’ screening decision is influenced by loan officers’ default rate, hence the loan officers are likely to focus on the better borrowers. However, crowdfunding emerged to provide finance to entrepreneurs who are less likely to meet the loan screening requirements. Thus, this study examined the interaction effect between loan officers’ characteristics and loan defaults on crowdfunding approval. We usedordered logistic regression to primary data collected from loan officers in microfinance institutions that are registered by the largest prosocial crowdfunding platform Kiva asfield partners. The study found a significant interaction effect of loan officers’ default rate and gender, experience and crowdfunding awareness. Thus, the results implied that, the demographic characteristics of the loan officers are interacted by the loan officers’ default rate when deciding to approve a loan for a crowdfunding campaign. Therefore, the findings recommended imparting loan officers with techniques that will help them keep a low default rate and those loan officers with a low default rate should work on crowdfunding approval